Health and Immune Boosting Techniques of General Adult Pakistani Population- A KAP Study - Khan, Iman; Farooqi, Shaheer; Vahidy, Ahmed Safi; Qamar, Mohammad Aadil; Dhillon, Rubaid Azhar; Azam, Ahmed (Journal of the Pakistan Medical Association, 2022)
Objective: To discover Pakistani adult population’s perception about their general health, immune status and knowledge regarding immunity, and to highlight their efforts to improve it. Method: The knowledge-attitude-practice study was conducted from January to May 2021, after approval ethics review committee of the Islamic International Medical College, Rawalpindi, Pakistan, and comprised individuals of either gender from the community aged 18 years or more and not suffering from any physical disability or mental illness. Data was collected using a pre-tested, self-administered questionnaire that was disseminated through online platforms. The collected data was analysed using SPSS 25. Results: All the 455(100%) individuals approached responded to the questionnaire. The mean age of the subjects was the mean age was 22.6±7.579 years. There were 256(56.3%) female respondents, 283(62.2%) were aged 20-21 years, and 359(78.9%) hailed for the Sindh province. Most participants perceived their general health as ‘good’ 197(43.3%). The immune system function was reported ‘good’ by 200(44%), and the perception of general knowledge of immunity was reported ‘good’ by 189(41.5%) subjects. Inverse relationships were identified between stress levels and self-perceived health, and between receiving effective homeopathic treatment and ‘very good’ self-perceived immune status (p<0.05). People willing to take non-obligatory vaccines had a positive opinion about their self-perceived knowledge on immunity that produced a direct relationship (p<0.05). Conclusion: The findings provide a framework of practices that should be promoted to improve health status of adult population in Pakistan. Key Words: Health status, Immunity, Attitude to health, Healthy lifestyle, Knowledge, Practices.